If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(2t+2)=2(5t+6)
We move all terms to the left:
6(2t+2)-(2(5t+6))=0
We multiply parentheses
12t-(2(5t+6))+12=0
We calculate terms in parentheses: -(2(5t+6)), so:We get rid of parentheses
2(5t+6)
We multiply parentheses
10t+12
Back to the equation:
-(10t+12)
12t-10t-12+12=0
We add all the numbers together, and all the variables
2t=0
t=0/2
t=0
| 2x^2-10x=22 | | 4(5m-4)=3(5m+13) | | 4(2g+2)=6(g+2) | | -3=5-2y | | x5 (10-11) = 2 | | 3e-3=42–2e | | 1/5x+1/3=−1/2x+8/3 | | 4(c+12)=+18 | | 2x²-4x-65=0 | | n+(–3.8)n=1.7 | | 4k-6-16/2k+3+2=0 | | 14z=7z-2+6z | | 4x2+3=-7x | | 1+5x=-7x+x | | -3=3/5n | | 12x+-5=4x+-37 | | 0.10(y-9)+0.08y=0.06-1.8 | | 4z/7-9=10 | | 220=1/2*h(15+29) | | 2(v+5)=7v-40 | | w/3+2w/4=10 | | 0.10(y-9)+0.08y=0.06y-1.8 | | 5(t-3)+7t=4(3t+5)-12 | | 7(t-2)+5t=4(3t+4)-12 | | X=7/4=2x-7/4 | | 9+6x=x+55 | | X+(4+2x)=188 | | 4c-14=-3c | | 4p+4=-4p+12 | | 2x-70=630 | | 3/2*(x+1)-5*(x-2)/6+3/4x=x-7/6+2*(2x+1)/3 | | 3/2(x+1)-5(x-2)/6+3/4x=x-7/6+2(2x+1)/3 |